(untitled) (Bioscience Journal, 2016)
The objective was to evaluate the effect of seed wheat coated with zinc, in its physiological, sanitary attributes and enzyme quality, during storage. We used two batches of seed, for seed treatment, we used commercial product as a source of zinc in the form of ZnSO4, along with fungicide and polymer. It was tested for levels 0, 1, 2, 3 and 4 mL ZnSO4 kg-1 seed. The physiological quality, during the storage period, was analyzed by the tests: moisture content, hectoliter weight, germination, emergence, index emergence rate, tetrazolium and sanity test. It was concluded that the doses 3 mL and 4 mL of ZnSO4 to assist in the ultimate expression of the seeds physiological quality, until six months stocked. This coating promotes a smaller reduction in the viability of seeds, furthermore, results in a lower incidence of fungi on seeds during storage. Also help to maximize the expression of physiological seed quality of higher and lower quality, respectively. The micronutrient zinc associated with fungicide and polymer had a lower incidence of fungi during the storage period.